Kecukupan Pasteurisasi Sistem Kontinyu Krimer Kental Manis dan Pengaruhnya Terhadap Stabilitas Selama Penyimpanan - Anis Zamaluddien; Feri Kusnandar; Eko Hari Purnomo (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
A sweetened condensed creamer (SCC) is a well-known dairy-based product used in various food products. SCC has pH of 6.00 and water activity (aw) of less than 0.8. A pasteurization process is applied in SCC processing to inactivate potential pathogenic microorganism in order to yield safely consumed product with a long shelf-life. The aim of this study was to evaluate thermal process adequacy of SCC in a commercial scale continuous pasteurization at 85°C and 95°C. Thermal process adequacy was determined by comparing the pasteurization value (P) of the process with standardized P value at different D cycles (2D, 3D, and 6D) of targeted microorganism and lipase enzyme. Pasteurization process at both 85°C and 95°C satisfactorily inactivated targeted microorganism (vegetative cells, coliform, yeast and mould, Salmonella, S aureus, and L monocytogenes). However, the designed pasteurization did not sufficiently inactivate lipase enzyme. SCC processed at 85°C had a longer shelf-life in term of its viscosity (292.4 days) than that of pasteurized at 95°C (174.5 days). Keywords: pasteurization value, rheology, shelf-life, sweetened condensed creamer, thermal process DOI: https://doi.org/10.29244/jmpi.2019.6.108